2013
DOI: 10.4161/rna.26541
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput screen identifies miRNA inhibitors regulating lung cancer cell survival and response to paclitaxel

Abstract: microRNAs (miRNAs) are small RNAs endogenously expressed in multiple organisms that regulate gene expression largely by decreasing levels of target messenger RNAs (mRNAs). Over the past few years, numerous studies have demonstrated critical roles for miRNAs in the pathogenesis of many cancers, including lung cancer. Cellular miRNA levels can be easily manipulated, showing the promise of developing miRNA-targeted oligos as next-generation therapeutic agents. In a comprehensive effort to identify novel miRNA-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 69 publications
2
30
0
Order By: Relevance
“…Reportedly, miR‐133a and miR‐133b could inhibit cell proliferation, migration and invasion in bladder cancer [27] and prostate cancer [28] by targeting the epidermal growth factor receptor (EGFR). A high‐throughput screen identified that miR‐133a and miR‐133b could decrease lung cancer cell survival by activating caspase‐3/7‐dependent apoptotic pathways and inducing cell cycle arrest in S phase [29]. Suppressive role of miR‐133a could also be found in esophageal squamous cell carcinoma [30], ovarian cancer [31], colorectal cancer [32] and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, miR‐133a and miR‐133b could inhibit cell proliferation, migration and invasion in bladder cancer [27] and prostate cancer [28] by targeting the epidermal growth factor receptor (EGFR). A high‐throughput screen identified that miR‐133a and miR‐133b could decrease lung cancer cell survival by activating caspase‐3/7‐dependent apoptotic pathways and inducing cell cycle arrest in S phase [29]. Suppressive role of miR‐133a could also be found in esophageal squamous cell carcinoma [30], ovarian cancer [31], colorectal cancer [32] and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The mutated putative miR-137 binding site in the SRC3 3'-UTR was generated using a Site-Directed Gene Mutagenesis kit (Beyotime Institute of Biotechnology, Haimen, China) according to the manufacturer's protocol. NSCLC cells were seeded at a density of ~1x10 5 cells/well into 24-well plates and cultured for 24 h prior to transfection. Co-transfections with 500 ng pGL3-Basic firefly luciferase reporter and 100 nM miR-137 mimic or scramble mimic into cells using Lipofectamine 2000 for 4 h at 37˚C was performed.…”
Section: Humanmentioning
confidence: 99%
“…Changes to the expression of microRNAs (miRNAs/miRs) in tumors are a focus being studied at present and it has been demonstrated that the dysregulation of miRNAs is involved in the malignancy of lung cancer (4,5). miRNAs are endogenous non-coding 19-23 nucleotide long RNA molecules that are located on chromosome 1p22.…”
Section: Introductionmentioning
confidence: 99%
“…Several such libraries have been developed and commercialized, enabling functional high-throughput, unbiased screens to be performed. This format has facilitated the identification of miRNAs that contribute to a variety of diseases and physiological responses, including viral infection 95 , breast cancer 96,97 and drug treatment responses 98,99 . A study involving both miRNA mimics and siRNA screening using the same assay, identified miRNAs involved in cisplatin resistance, as well as the kinases targeted by these miRNAs 100 .…”
Section: Figurementioning
confidence: 99%